The Effect of Toll Road Construction on The Daily Income at PT. Jasa Marga (Persero) Tbk - Noor, Sa'ad; Yulianty, Detty; Setiana, Nana (Dinasti Publisher, 2025)
The study aims to determine the influence of each toll road construction segment on the daily income. The research employed a quantitative method to get an overview of the daily income at PT. Jasa Marga (PERSERO) Tbk. The results of this study showed: correlation coefficient analysis, determination test, simple regression test, and descriptive statistical analysis. The results revealed that there was a correlation coefficient between